Cabozantinib plus atezolizumab versus sorafenib for advanced hepatocellular carcinoma (COSMIC-312): a multicentre, open-label, randomised, phase 3 trial. Issue 8 (August 2022) - Kelley, Robin Kate; Rimassa, Lorenza; Cheng, Ann-Lii; Kaseb, Ahmed; Qin, Shukui; Zhu, Andrew X; Chan, Stephen L; Melkadze, Tamar; Sukeepaisarnjaroen, Wattana; Breder, Valery; Verset, Gontran; Gane, Edward; et al.
Summary: Background: Cabozantinib has shown clinical activity in combination with checkpoint inhibitors in solid tumours. The COSMIC-312 trial assessed cabozantinib plus atezolizumab versus sorafenib as first-line systemic treatment for advanced hepatocellular carcinoma. Methods: COSMIC-312 is an open-label, randomised, phase 3 trial that enrolled patients aged 18 years or older with advanced hepatocellular carcinoma not amenable to curative or locoregional therapy and previously untreated with systemic anticancer therapy at 178 centres in 32 countries. Patients with fibrolamellar carcinoma, sarcomatoid hepatocellular carcinoma, or combined hepatocellular cholangiocarcinoma were not eligible. Tumours involving major blood vessels, including the main portal vein, were permitted. Patients were required to have measurable disease per Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1), Barcelona Clinic Liver Cancer stage B or C disease, an Eastern Cooperative Oncology Group performance status of 0 or 1, adequate organ and marrow function, and Child-Pugh class A. Previous resection, tumour ablation, radiotherapy, or arterial chemotherapy was allowed if more than 28 days before randomisation. Patients were randomly assigned (2:1:1) via a web-based interactive response system to cabozantinib 40 mg orally once daily plus atezolizumab 1200 mg intravenously every 3 weeks, sorafenib 400 mg orally twice daily, or single-agent cabozantinib 60 mg orally once daily. Randomisation was stratified by disease aetiology, geographical region, and presence of extrahepatic disease or macrovascular invasion. Dual primary endpoints were progression-free survival per RECIST 1.1 as assessed by a blinded independent radiology committee in the first 372 patients randomly assigned to the combination treatment of cabozantinib plus atezolizumab or sorafenib (progression-free survival intention-to-treat [ITT] population), and overall survival in all patients randomly assigned to cabozantinib plus atezolizumab or sorafenib (ITT population). Final progression-free survival and concurrent interim overall survival analyses are presented. This trial is registered with ClinicalTrials.gov, NCT03755791 . Findings: Analyses at data cut-off (March 8, 2021) included the first 837 patients randomly assigned between Dec 7, 2018, and Aug 27, 2020, to combination treatment of cabozantinib plus atezolizumab (n=432), sorafenib (n=217), or single-agent cabozantinib (n=188). Median follow-up was 15·8 months (IQR 14·5–17·2) in the progression-free survival ITT population and 13·3 months (10·5–16·0) in the ITT population. Median progression-free survival was 6·8 months (99% CI 5·6–8·3) in the combination treatment group versus 4·2 months (2·8–7·0) in the sorafenib group (hazard ratio [HR] 0·63, 99% CI 0·44–0·91, p=0·0012). Median overall survival (interim analysis) was 15·4 months (96% CI 13·7–17·7) in the combination treatment group versus 15·5 months (12·1–not estimable) in the sorafenib group (HR 0·90, 96% CI 0·69–1·18; p=0·44). The most common grade 3 or 4 adverse events were alanine aminotransferase increase (38 [9%] of 429 patients in the combination treatment group vs six [3%] of 207 in the sorafenib group vs 12 [6%] of 188 in the single-agent cabozantinib group), hypertension (37 [9%] vs 17 [8%] vs 23 [12%]), aspartate aminotransferase increase (37 [9%] vs eight [4%] vs 18 [10%]), and palmar-plantar erythrodysaesthesia (35 [8%] vs 17 [8%] vs 16 [9%]); serious treatment-related adverse events occurred in 78 (18%) patients in the combination treatment group, 16 (8%) patients in the sorafenib group, and 24 (13%) in the single-agent cabozantinib group. Treatment-related grade 5 events occurred in six (1%) patients in the combination treatment group (encephalopathy, hepatic failure, drug-induced liver injury, oesophageal varices haemorrhage, multiple organ dysfunction syndrome, and tumour lysis syndrome), one (<1%) patient in the sorafenib group (general physical health deterioration), and one (<1%) patient in the single-agent cabozantinib group (gastrointestinal haemorrhage). Interpretation: Cabozantinib plus atezolizumab might be a treatment option for select patients with advanced hepatocellular carcinoma, but additional studies are needed. Funding: Exelixis and Ipsen.